'We are analogue in a digital world': an anthropological exploration of ontologies and uncertainties around the proposed Konza Techno City near Nairobi, Kenya. Issue 2 (4th May 2017) - Van den Broeck, Jan
Abstract : Envisioned as an inclusive new city and a major technology hub, Konza Technology City is said to bring stability and growth to Nairobi's south-eastern periphery. However, for the communities living in its vicinity, the advent of this new urban core is suffused with uncertainties as its existence largely takes place in the imaginary realm of plans and billboards of which the outcome is unforeseeable today. This article is an anthropological exploration of these uncertainties and of the concept of uncertainty in general. I start this exploration with an analysis of the notions of the 'analogue' and the 'digital' that are locally used to describe increased societal pluralism and differentiation in the area under the influence of the Konza Technology City and in which social and material worlds appear intricately entwined. Subsequently, I argue that these multiplicities and the uncertainties that are inseparable from them are best approached ontologically. I maintain that such an approach engenders an understanding of ontologies as being inherently plural, subjunctive, future oriented and, thus, immanently uncertain. Here, ontological uncertainty emerges as a highly productive force as it engenders hope and possibility and enables people to anticipate the materialization of multiple futures and realize multiple potentialities.